2015
DOI: 10.1063/1.4930833
|View full text |Cite|
|
Sign up to set email alerts
|

Electrical spin injection in modulation-doped GaAs from an in situ grown Fe/MgO layer

Abstract: We study spin accumulation in n-doped GaAs that were electrically injected from Fe via MgO using three-terminal Hanle measurement. The Fe/MgO/GaAs structures were prepared in a cluster molecular beam epitaxy that did not require the breaking of the vacuum. We found the crystal orientation relationship of epitaxial structures Fe[100]//MgO[110]//GaAs[110] without evident defects at the interface. Control of depletion width and interface resistance by means of modulation doping improves spin injection, leading to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In the work presented here, the spin-polarization as a function of temperature using an Fe contact on an InGaAs quantum well LED device is investigated where the transfer between the III-V and metals growth chamber was carried out in situ under strict UHV conditions [10,14]. Recent electrical spininjection measurements on the Fe/MgO/GaAs combination have demonstrated that low defect levels at the MgO/GaAs interface can be achieved by in situ wafer transfer [15].…”
Section: Introductionmentioning
confidence: 99%
“…In the work presented here, the spin-polarization as a function of temperature using an Fe contact on an InGaAs quantum well LED device is investigated where the transfer between the III-V and metals growth chamber was carried out in situ under strict UHV conditions [10,14]. Recent electrical spininjection measurements on the Fe/MgO/GaAs combination have demonstrated that low defect levels at the MgO/GaAs interface can be achieved by in situ wafer transfer [15].…”
Section: Introductionmentioning
confidence: 99%
“…In reality, the FM/SC interface mixing, magnetic dead layer, and conductivity mismatch are however the major obstacles for the electrical spin injection, which limit the efficiency generally below ~10% at RT (ambiguity may exist here due to the different definitions) [38,39,43,543,544]. This situation was later partly relieved by efforts of either inserting spin-dependent tunneling barriers [545,546] or including mild post-growth thermal treatments [35,36,39]. On the other hand, advanced microscopy techniques have been developed and revealed some interesting phenomena unique to the nonlocal devices [547,548].…”
Section: Lateral Devicesmentioning
confidence: 99%
“…Only recently with proper interface engineering, evidence of appreciable spin injection efficiency has been practically demonstrated up to RT for some specific systems [525,558,560]. It can be summarized from those successful studies that a diffusion barrier which can be a tunnel barrier oxide or even an ultrathin FM might be required to avoid elemental migration from the Heusler alloys into GaAs [525]; while for magnetite (and as well for Fe [546]), a high-quality MgO barrier which can be epitaxially grown between Fe3O4 and GaAs is mandatory for preserving the high spin polarization of the magnetic oxide and simultaneously for achieving abrupt interfaces for efficient spin injection at RT [560].…”
Section: Lateral Devicesmentioning
confidence: 99%